Evaluation of asthma improvement after endoscopic sinus surgery in nasal polyposis - fariba Rezaeetalab; Morteza Noorollahian; Hadi Akbari; Gholamhosein Rezaeetala (Iranian Journal of Otorhinolaryngology, 2008)
Introduction: Asthma is characterized by airway inflammation, airway hyper responsiveness, and reversible airflow limitation. The prevalence of the disease has increased over 2 decades to approximately 5 to 10% of the population. The presence of nasal polyposis in asthma patients is associated with increase in asthma severity. We attempted to determine the efficacy of endoscopic sinus surgery in patients with asthma and nasal polyposis. Materials and Methods: We performed a prospective, cross-sectional study from 2001 until 2006. This study included 50 patients with severe persistent asthma and nasal polyposis. The severity of asthma (in NHLBI and NAPP) and FEV1 before and after endoscopic nasal polypectomy was recorded. We used paired simple T test for comparation of data mean.The gathered data were analyzed with SPSS software. Results: In this study, median ages are 32.5 ± 14.3  years. Male to female is 2.3 to 1. All of patients have severe persistent asthma and nasal polyposis. From 50 patients with asthma and nasal polyposis, in 38 cases asthma severity and FEV1 were improved. (mean of  FEV1 before endoscopic  sinus polypectomy = 1.68 L ,  mean of FEV1 after endoscopic sinus polypectomy = 2.52 L).  Conclusion: Opening of upper airway and improvement of breathing through sinus endoscopy induce betterment of asthma severity, though the possibility of nasal polyposis should be investigated and treatment with endoscopic sinus surgery planned accordingly.